2015
DOI: 10.1093/gbe/evv046
|View full text |Cite
|
Sign up to set email alerts
|

OASes and STING: Adaptive Evolution in Concert

Abstract: OAS (2′–5′-oligoadenylate synthases) proteins and cyclic GMP–AMP synthase (cGAS, gene symbol: MB21D1) patrol the cytoplasm for the presence of foreign nucleic acids. Upon binding to double-stranded RNA or double-stranded DNA, OAS proteins and cGAS produce nucleotide second messengers to activate RNase L and STING (stimulator of interferon genes, gene symbol: TMEM173), respectively; this leads to the initiation of antiviral responses. We analyzed the evolutionary history of the MB21D1–TMEM173 and OAS–RNASEL axe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 87 publications
(145 reference statements)
1
43
0
Order By: Relevance
“…This particular SNP is the second most frequent in the population, and has been previously reported as a loss-of-function human STING variant where it exhibits greater than 90% loss in the ability to induce IFNβ production 63 There are 6 positively selected amino acids of STING in bats, with 3 of these residues located in the transmembrane domain that are important for protein dimerization 64 . It has also been found that residue 230 in primate and bat phylogenies is undergoing positive selection.…”
Section: Immunoprecipitations and Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular SNP is the second most frequent in the population, and has been previously reported as a loss-of-function human STING variant where it exhibits greater than 90% loss in the ability to induce IFNβ production 63 There are 6 positively selected amino acids of STING in bats, with 3 of these residues located in the transmembrane domain that are important for protein dimerization 64 . It has also been found that residue 230 in primate and bat phylogenies is undergoing positive selection.…”
Section: Immunoprecipitations and Western Blotsmentioning
confidence: 99%
“…It has also been found that residue 230 in primate and bat phylogenies is undergoing positive selection. This site is also polymorphic in the human population as G230A, and the residue is located in the loop region of STING, which is predicted to form a lid that covers the CDN binding pocket 64 . 68,71 .…”
Section: Immunoprecipitations and Western Blotsmentioning
confidence: 99%
“…The OAS2 protein is a well-known innate immune activated antiviral enzyme catalyzing synthesis of 2′-5′-oligoadenylate for RNase L activation and inhibition of viral propagation9. More recent studies show that it also participates in other biological processes.…”
mentioning
confidence: 99%
“…The residue that exhibits the most variation across primates is residue 54, which has been shown to be under positive selection in human, chimpanzee, and gorilla as well as under balancing selection in chimpanzee and macaque (Ferguson, et al 2012; Fish and Boissinot 2015; Mozzi, et al 2015). In OWM, ancestral Arg predominates followed in commonality by Cys and lastly His and Tyr.…”
Section: Resultsmentioning
confidence: 99%
“…selection in favor of amino acid changes. Evolutionary analyses across Primates and Chiroptera have reported accelerated evolution of OAS genes, particularly for OAS1 (Hancks, et al 2015; Mozzi, et al 2015). Moreover, house mouse, chimpanzee, and macaque populations have been shown to harbor an extremely high level of polymorphism at OAS1 denoting the action of balancing selection at this locus (Ferguson, et al 2012; Ferguson, et al 2008; Fish and Boissinot 2015).…”
Section: Introductionmentioning
confidence: 99%